Influence of Polyvinyl Alcohol (PVA) on quantitative phase development during early cement hydration - Jansen, Daniel; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen; Hergeth, Wolf Dieter; Härzschel, Reinhard (17. Internationale Baustofftagung - Tagungsbericht, 2009)
Investigations into the influence of various polyvinyl alcohols (PVOH) on the hydration of Portland cement have shown that the alumina reaction is affected during the cement hydration. It was found that the dissolving of the sulfate carrier and of the C 3 A is retarded by the presence of polyvinyl alcohols and also that the ettringite formation is accelerated after about 16 hours hydra - tion. These results were obtained with 3 different polyvinyl alcohols.
UnivIS-Import:2015-04-16:Pub.2009.nat.dgeo.IGM.LM.influe